Circulation as a Basic of Animal Sheep Design in Gianyar-Bali - Asthabayu, I Made Angga Dhimas; Salain, Putu Rumawan; Primayatna, Ida Bagus Gde (Journal of A Sustainable Global South; Vol 2 No 1 (2018): February 2018, 2020)
Gianyar Regency has a arrractive tourist destinations for visitor domestic and foregin visitor. In addition society and vis-itors have a rate of consumption of beef or pork are quite high, where the Gianyar Regency has no industry to accom-modate animal cuts service to meet the needs of consumers will be the meat. One offort to accommodate the need of the meat is the establishment of industry and services in the form of Slaughterhouse Animals  that would later embody the need for meat in Gianyar Regency. Circulation as the Basis for the design of the RPH has a pupose to provide comfort on visitors or animals. Which would later effect the comfort of the visitors  and the result will be the meat of the animal after the cut. Circulation as the basis for the design of Slaughterhouse Animal in Gianyar describe using the methods of analysis comparisons against Animal Slaughterhouse design ang evaluation methods. After analyzing the in accordance with the discussion against on the design of this, carried outan evaluation to find out how circulation pat-terns on an industry are. So that in the future, the result of the evaluaton will be useful as a reference in designing an industrial area especially in the design of Slaughterhouse Animals. Index Terms — Circulation, Design, Slaughterhouse Animals.